Economic aspects of the DHIS2 contact tracing system as part of the COVID-19 strategy in Tromsø municipality - Sanoja, Johanna (UiT Norges arktiske universitet, 2022)
Background: The corona virus pandemic caused by the SARS-CoV-2 virus begun in Norway in 2020. The Norwegian government decided that test-identify-trace-quarantine is the main national strategy fighting against the pandemic. From municipalities this required contact tracing actions to maintain the number of transmissions as low as possible. There was no earlier experience of contact tracing of this scale, nor knowledge of resources required from municipalities. Objective: The objective of this study was to estimate the resources needed for implementing and running a contact tracing function in a municipality, using Tromsø as an example. We aimed to describe a resource frame for contact tracing related to COVID-19. Data and methods: A mixed methods costing study was conducted, including COVID-19 index cases and close contacts registered on DHIS2 system used by Tromsø municipality, and cost related estimates from several sources. Probabilistic sensitivity analyses run as Monte Carlo simulation to cover the uncertainty in the data. Results: During 2020 in Tromsø municipality there were in the DHIS2 system registered 644 positive cases with SARS-CoV-2 virus, and 587 close contacts. With 95 percent uncertainty interval (NOK 557 149 – NOK 796 839), total cost of contact tracing was NOK 666 946 during 2020 for the municipality of Tromsø with population of 76 974 persons. Estimated costs for other hypothetical municipalities with populations of 1000 and 200 000 persons were NOK 60 003 and NOK 1 669 463, respectively. Conclusion: The cost of contact tracing facility in Tromsø was approximately NOK 670 000 during 2020, but the results are highly uncertain.